Novel compound heterozygous variants in the LHCGR gene identified in a subject with Leydig cell hypoplasia type 1 - Xu, Yufei; Chen, Yulin; Li, Niu; Hu, Xuyun; Li, Guoqiang; Ding, Yu; Li, Juan; Shen, Yiping; Wang, Xiumin; Wang, Jian (Journal of Pediatric Endocrinology & Metabolism, 2018)
Leydig cell hypoplasia (LCH) is a rare disease and one of the causes of male disorder of sexual differentiation (DSD). Inactivating mutations in the luteinizing hormone/chorionic gonadotropin receptor (LHCGR) gene account for the underlying LCH pathogenicity. This study aimed to analyze the clinical presentation and diagnosis as well as highlight the molecular characteristics of a subject with LCH type 1. Clinical data were collected from the subject and analyzed. Next generation sequencing of the immediate family pedigree using peripheral blood genomic DNA was performed, and the relevant mutations were verified with Sanger sequencing. We describe the case of a 5-year-old patient with DSD, presenting with a lateral inguinal hernia accompanied by abnormal hormone tests. The genetic analysis revealed novel compound heterozygous variants in the LHCGR gene, including a splice site mutation (c.681-1 G>A) and a frameshift variant (c.1582_1585del ATAT, p.Ile528*). We identified novel compound heterozygous variants in the LHCGR gene, and expanded the genotype-phenotype correlation spectrum of LHCGR variants.